Teachers' Attitudes toward Problem Texts in Literature Classes - Sabina Viscek (University of Maribor Press, 2014)
Contemporary youth literature is characterised by deviation from the traditional pattern of obedient child and a happy childhood. The topics on which the writers in Slovenia in the seventies and especially in the nineties openly wrote, have become problem or taboo - so denoted by certain groups, especially those of teachers and parents. The article presents the views of Slovenian primary school teachers and teachers of Slovenian towards discussing problem texts in literature classes in basic school. On the basis of empirical non-experimental research, which included 33 teachers of Slovenian and 58 primary school teachers, statistically significant difference in defining the suitability of topics, and in relation to problem texts have been found.